Water‐Catalyzed Oxidation of Few‐Layer Black Phosphorous in a Dark Environment. (30th June 2017) - Hu, Zehua; Li, Qiang; Lei, Bo; Zhou, Qionghua; Xiang, Du; Lyu, Zhiyang; Hu, Fang; Wang, Junyong; Ren, Yinjuan; Guo, Rui; Goki, Eda; Wang, Li; et al.
Abstract: Black phosphorus (BP) shows great potential in electronic and optoelectronic devices owing to its semiconducting properties, such as thickness‐dependent direct bandgap and ambipolar transport characteristics. However, the poor stability of BP in air seriously limits its practical applications. To develop effective schemes to protect BP, it is crucial to reveal the degradation mechanism under various environments. To date, it is generally accepted that BP degrades in air via light‐induced oxidation. Herein, we report a new degradation channel via water‐catalyzed oxidation of BP in the dark. When oxygen co‐adsorbs with highly polarized water molecules on BP surface, the polarization effect of water can significantly lower the energy levels of oxygen (i.e. enhanced electron affinity), thereby facilitating the electron transfer from BP to oxygen to trigger the BP oxidation even in the dark environment. This new degradation mechanism lays important foundation for the development of proper protecting schemes in black phosphorus‐based devices.